2007
DOI: 10.1203/pdr.0b013e31813cbe7a
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Content and Body Composition in Overweight Children and Adolescents

Abstract: ABSTRACT:The aim of this study was to analyze the bone mineral content (BMC) of the skeleton and the body composition in lean and fat masses in a population of young overweight subjects, before diet or medical intervention. A total of 496 white youths (298 females, 198 males) were studied. Their body mass index (BMI) values were 29.2 Ϯ 5.5 kg/m 2 in females and 28.3 Ϯ 5.1 kg/m 2 in males, corresponding to relative weights (wts) [actual wt, W, divided by the mean wt normal for height (ht), Wi] of 1.55 Ϯ 0.24 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
2
2
0
Order By: Relevance
“…But this method is only adapted on regional DXAs and loses the third dimension of the bone (depth), which is important in small bones. As demonstrated in several previous pediatric studies, the TBMC is highly dependent on the anthropometric values of children from birth to adolescence, specifically for the weight‐bearing skeleton . In our study, we found a close linear relationship between weight and TBMC measurements (data not shown).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…But this method is only adapted on regional DXAs and loses the third dimension of the bone (depth), which is important in small bones. As demonstrated in several previous pediatric studies, the TBMC is highly dependent on the anthropometric values of children from birth to adolescence, specifically for the weight‐bearing skeleton . In our study, we found a close linear relationship between weight and TBMC measurements (data not shown).…”
Section: Discussionsupporting
confidence: 84%
“…As demonstrated in several previous pediatric studies, the TBMC is highly dependent on the anthropometric values of children from birth to adolescence, specifically for the weight-bearing skeleton. 19,24,29,33,34 In our study, we found a close linear relationship between weight and TBMC measurements (data not shown). That's why we have chosen (1) to study a TBMC instead of density and (2) to match it with the ideal weight for a child with the same height.…”
Section: Discussionsupporting
confidence: 59%
“…However, the effects of body mass on the skeleton remain controversial although well documented in obese subjects in previous studies [35,36]. Some studies have shown that obese subjects have weaker bone to bear their over-weight body mass compared to normal counterparts in both humans and animals [37,38]. In our study, after adjusting for body mass (unpublished data), no significant differences in bone traits between the obese and normal weight mice were found.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that weight, BMI, waist circumference, and fat mass index in normal children was higher than those in children with low lumbar bone mass. Previous investigations in France ( 22 , 23 ), the Netherlands ( 4 ), and Italy ( 24 ) also showed that bone mineral density was correlated with obesity, and fat mass. Body weight might improve bone mineralization due to the mechanical loading on weight-bearing bones ( 25 - 27 ).…”
Section: Discussionmentioning
confidence: 76%